“It is Impossible to Liken Solovetsky Island to Mount Athos.” - Tatiana A. Isachenko; Татьяна Александровна Исаченко (Russian State Library, 2015)
The article represents a review of the book “Brief Narration about What the Difference between Holy Mount Athos and the Solovetsky Monastery Is, and What the Difference between the Holy Mount’s Monasteries and the Solovetsky Cloister Is” - a monument of handwritten literature of the 17th century with Athos’ description. The edition, consecrated to the 1000th anniversary of the Old Russian Monasticism on Athos, was published with the assistance of the Russian Fund for Humanities and is provided with an erudite commentary of the doctor of philological sciences T. A. Isachenko. Рецензия на книгу «Краткое повествование, чем разнствует Святая Гора Афон от нашего Соловецкого монастыря, и чем разнствуют монастыри Святой Горы от обители Соловецкой» - памятник рукописной книжности XVII в. с описанием Афона. Издание, посвященное 1000-летию древнерусского монашества на Афоне, подготовлено при поддержке Российского гуманитарного научного фонда и снабжено научным комментарием доктора филологических наук Т. А. Исаченко.